2013
DOI: 10.1007/s00737-013-0353-z
|View full text |Cite
|
Sign up to set email alerts
|

Detection of antenatal depression in rural HIV-affected populations with short and ultrashort versions of the Edinburgh Postnatal Depression Scale (EPDS)

Abstract: Risk of antenatal depression has been shown to be elevated in Southern Africa and can impact maternal and child outcomes, especially in the context of the Human Immunodeficiency Virus (HIV). Brief screening methods may optimize access to care during pregnancy, particularly where resources are scarce. This research evaluated shorter versions of the Edinburgh Postnatal Depression Scale (EPDS) to detect antenatal depression. This cross-sectional study at a large primary health care (PHC) facility recruited a cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
99
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 84 publications
(105 citation statements)
references
References 60 publications
4
99
2
Order By: Relevance
“…Among Xhosa-speaking women, several studies have supported the construct validity, criterion-related validity, and factor structure of the EPDS-10 (De Bruin et al 2004; Hartley et al 2011; Lawrie et al 1998), and it has also been shown to have a high sensitivity for detecting postnatal depression in numerous other settings worldwide (Tsai et al 2013). Similar to Kabir et al (2008) and Rochat et al (2013), we defined 4 short and ultra-short versions of the EPDS-10: the 2-item analogue of the Patient Health Questionnaire (EPDS-2) (Lowe et al 2005; Monahan et al 2009), the 3-item anxiety subscale (EPDS-3), an abbreviated 5-item version of the depressive symptoms subscale (EPDS-5) (Rochat et al 2013), and the 7-item depressive symptoms subscale (EPDS-7) (Box 1). Following previous studies in this population, we employed a cutoff score of EPDS-10 ≥13 to define the criterion standard of probable antenatal depression (Honikman et al 2012; Rochat et al 2006; Tomlinson et al 2013).…”
Section: Methodssupporting
confidence: 69%
See 2 more Smart Citations
“…Among Xhosa-speaking women, several studies have supported the construct validity, criterion-related validity, and factor structure of the EPDS-10 (De Bruin et al 2004; Hartley et al 2011; Lawrie et al 1998), and it has also been shown to have a high sensitivity for detecting postnatal depression in numerous other settings worldwide (Tsai et al 2013). Similar to Kabir et al (2008) and Rochat et al (2013), we defined 4 short and ultra-short versions of the EPDS-10: the 2-item analogue of the Patient Health Questionnaire (EPDS-2) (Lowe et al 2005; Monahan et al 2009), the 3-item anxiety subscale (EPDS-3), an abbreviated 5-item version of the depressive symptoms subscale (EPDS-5) (Rochat et al 2013), and the 7-item depressive symptoms subscale (EPDS-7) (Box 1). Following previous studies in this population, we employed a cutoff score of EPDS-10 ≥13 to define the criterion standard of probable antenatal depression (Honikman et al 2012; Rochat et al 2006; Tomlinson et al 2013).…”
Section: Methodssupporting
confidence: 69%
“…However, it is also notable that, although determinations based on the conventional EPDS-10 threshold of ≥13 are commonly assumed to result in over-diagnosis, this has actually not been found to be the case in IsiZulu-speaking South African women. In a study conducted among pregnant women in rural KwaZulu-Natal, the prevalence of major depressive disorder as determined by structured clinical interview (47%) closely matched the prevalence of probable depression as determined using the EPDS-10 (44%) (Rochat et al 2011; Rochat et al 2013). …”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The EPDS score was obtained by summing all item scores, creating a continuous variable. A cutoff score of 13 [16, 28, 33] was used to categorise the sample into distressed and non-distressed respondents.…”
Section: Methodsmentioning
confidence: 99%
“…24 Broadly, inverse probability of missingness weights allow fully observed individuals to "standin" for partially observed individuals. For example, consider a study of 500 women and 500 men, in which 100 women and 200 men were missing a measurement of outcome.…”
Section: Inverse Probability Weightingmentioning
confidence: 99%